ANALISIS DETERMINAN AUDIT DELAY (Studi Empiris Pada Perusahaan Property dan Real Estate Yang Terdaftar Di Bursa Efek Indonesia Pada Tahun 2012-2014) - Aviantara Sains Kesuma; Tona Aurora L; Asep Machpuddin (Magister Ilmu Akuntansi Universitas Jambi, 2016)
The purpose of this study was to determine and obtain empirical evidence that factors affecting audit delay. The factors examined in this study is the size of the company, the auditor's opinion, a public accounting firm size, profitability, solvency, the complexity of the company's operations. Until this research is a property dan real estate company listed on the Indonesian stock exchange in 2012-2014. Purposive sampling based on the results obtained 15 property dan real estate companies that meet the criteria of the sample. Testing this hypothesis using multiple linear regression analysis. Hypothesis testing results show that the auditor's opinion, the profitability and complexity of the company's operations influence on audit delay. Hypothesis testing results also show that the size of the firm, the firm size and solvency has no influence on audit delay.